Theorizing relational people management in micro enterprises: a multi-theoretical perspective - Nalweyiso, Grace; Mafabi, Samuel; Kagaari, James; Munene, John; Abaho, Ernest (Emerald, 2022)
Purpose This paper offers a theoretical explanation to a positive story of a micro enterprise found in Uganda, an African developing country that has successfully managed workplace relationships, its survival and good performance. Specifically, the paper examines multiple theories to explain the practice in this enterprise. Design/methodology/approach The study uses storytelling, a form of narrative inquiry embedded in qualitative methodology. Based on in-depth interviews with the owner-manager and employees, a story was developed detailing their practical experience while focusing on the context, actions, results and lessons. Findings Findings reveal that micro enterprises that allow free generation of ideas across all levels with optimistic people who reciprocate and work together create a friendly work atmosphere with support for one another, with the ability to amicably resolve conflicts and build trust. More so, theories including social exchange theory, relational cohesion theory, complex adaptive systems theory and cultural historical activity theory help explain the manifestations of relational people management in micro enterprises. Originality/value This paper is unique in its use of a positive story showing a practical experience of how workplace relationships are managed in a micro enterprise found in Uganda. In addition, a multi-theoretical perspective is used to explain the manifestations in the story which may be novel in the study context. Thus, a conceptual model is proposed depicting generalized reciprocity, positive emotions, generative leadership and relational agency as antecedents of relational people management with relational agency again mediating the other relationships.